Determinación de escopolamina en muestras de orina mediante el método de cromatografía en capa fina, que ingresan al laboratorio de química forense del departamento de criminalística de chimborazo durante el período abril- agosto 2010. - Ortiz Guerrero, María Fernanda (2011)
It has done this work as a useful tool to society, serving the legal and Analyst Medical Toxicology, as this type of research is unique in the province considering the time and place in which was carried out, Which as a data collection bibliographic, statistical background collected in the Forensic Chemistry Laboratory, Department of Criminology of the Province of Chimborazo in the period from April to august of 2010, since escopolamina has become a social problem of public health, because the individual who consumes this toxic endangers their physical, mental, family, and even death.